Does customer relationship strategy influence customer satisfaction and loyalty?: Evidence from Malaysia banking sector - Salimon, Maruf Gbadebo; Yusoff, Rushami Zien; Abdullateef, Aliyu Olayemi (2013)
Purpose – The main purpose of this paper is to develop a conceptual framework that explains the influence of Customer Relationship Strategy on the customer satisfaction and loyalty of Malaysia Banks.Design/methodology/approach – This paper adopts qualitative method of reviewing related literatures.Findings – Evidences from the extant literatures have suggested that effective implementations of the five dimensions of CRM (Customer Orientation, CRM Organization, Knowledge Management, Technology Based CRM and Customer Involvement) will positively affect customer satisfaction and lead to loyalty within the banking industry.Research limitations/implications – The major limitation of this work is that it is qualitative and thereby requires empirical data to support the model that is presented. Practical implications – This paper practically suggests that for banks to gain satisfaction and loyalty of their customers, they must monitor level of customer trust through proper integration of CRM application.Originality/value – This paper primarily conceptualizes a measurement model that would assist in determining the impacts of CRM on customer satisfaction and loyalty of banks.It is the first study that incorporates customer involvement dimension along other four CRM dimensions that was developed by Sin et al (2005). It also considers trust as a moderating variable between satisfaction and loyalty.